2019
DOI: 10.22161/ijeab.4448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Heavy Metal on Stress-Related Genes in Tomato (Solanumlycopericum L.) Plants

Abstract: Heavy metal pollution is a major environmental problem all over the world. It is known that high concentration of heavy metals in soils and waters cause genotoxicity and damage to most of the functional biomolecules. The aim of this study was to determine the molecular changes in tomato ( Solanum lycopericum L.) genome under heavy metal of zinc stress. Zinc is a microelement which should be taken in very less amounts by plants, animals and humans. In plants, zinc in low concentration is essential for root and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Metallothionein binding proteins (MTs) protect plants from metal stress and toxicity. Numerous studies have shown that MTs are highly expressed in many plants exposed to heavy metal toxicity [7,8,27]. Cysteine residue has the ability to bind heavy metals both physiologically (such as zinc, copper, and selenium) and xenobiotically (such as cadmium, mercury, silver, and arsenic) via thiol groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Metallothionein binding proteins (MTs) protect plants from metal stress and toxicity. Numerous studies have shown that MTs are highly expressed in many plants exposed to heavy metal toxicity [7,8,27]. Cysteine residue has the ability to bind heavy metals both physiologically (such as zinc, copper, and selenium) and xenobiotically (such as cadmium, mercury, silver, and arsenic) via thiol groups.…”
Section: Resultsmentioning
confidence: 99%
“…It plays a critical role in the defense system against ROS, which occurs as a result of stress factors, by maintaining the GSH level and acts as a substrate for glutathione-Stransferases. In many recent studies, it was stated that GR-1 expression increased against cadmium stress in various plants [7,9,[31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations